Generalized Correlation for the Physical and Psychometric Properties of Chlorodifluromethane - Ismail, Natheer Nori (Nahrain University College of Engineering Journal, 2014)
Chlorodifluoromethane is used as pure or inmixture for refrigeration (medium-hightemperatures). It is also used as a blowing agentfor extruded polystyrene and polyurethane foamsand a component in sterilant gas mixtures. Anewgeneralized correlation for the physical andpsychometric properties of liquidChlorodifluromethane as a function totemperature are introduced, Equation (1). Thenew correlation was statistically compared withthose previously presented and found to be:3DT2Property? A ? BT ? CT ? …(1)WhereA, B, C and D are the property constants,T is the temperature in degrees centigrade.